Performing authenticities : cultural forms and their functions in the Reclaim the Streets -protest - Yliselä, Aura (2007)
In this thesis I study the role of culture in the context of social movements. I argue that the role of concrete cultural forms in protest movements’ action has undergone a rather small interest in the Finnish study of social movements. I examine culture in social movements by looking at the “cultural turn” in social sciences, the rise of “new social movements” and through the theorizing of Pierre Bourdieu, Sarah Thornton and Ron Eyerman and Andrew Jamison. I conceptualize culture as both the concrete cultural praxis (e.g. music, art, dancing) and as a semiotic and cognitive system behind all action. As an empirical case study, I adopt a cultural perspective towards one protest movement, the Finnish Reclaim the Streets –movement, which I consider as a cultural and expressive form of collective action. The Reclaim the Streets -demonstrations are political carnivals, acts of non-violent civil disobedience. The idea is to block a city street from car traffic for couple of hours or one day. A party is held on the street. The idea behind the protest is a critique of private traffic and of global capitalism. Using qualitative methods I examine the role of concrete cultural forms, such as music, visual art and bodily habitus in the Reclaim the Streets –protest. My empirical data consists of 5 theme interviews with the protestors, analysis of flyers, posters and www-pages produced by the activists (micro-media) and an ethnographical participatory observation with one activist group in organizing a Reclaim the Streets –event, and attending 3 Reclaim the Streets –protests in 2 different Finnish cities. I analyze this data qualitatively by looking up themes according to my research questions. The results of my thesis show that the cultural forms that the protestors are using have important functions in the protest. I divide these functions to pragmatic and symbolic functions. The pragmatic functions are related to the protestors’ subcultural capital, their ability to utilize subcultural resources and cultural meanings in order to recruit sympathizers and make the protest event work. On a symbolic level, according to my theoretical interpretation the cultural forms are representing a counter-cultural authenticity which opposes a constructed commercial mainstream. I theorize that this performed countercultural authenticity is an important aspect in producing the movement’s cohesion and cognitive praxis in Eyerman and Jamison’s terms.